A structure and maintenance of the program of development of coordination capabilities of juvenile volleyball players at a stage of initial preparation. - Boychuk R.I (Kharkov National Pedagogical University, 2010)
Means and methodical acceptances of development of coordination capabilities of juvenile sportsmen are considered. 40 sportsmen participated in experiment. For a factor analysis it selected eight most significant parameters for the given age. Parameters of development are defined: capabilities to reproduction of spatial parameters of movements; capabilities to differentiating of time intervals; capabilities to reproduction of muscular gains; capabilities to an alining in space; vestibular durability. The program of their development at a stage of initial preparation is offered.